2019
DOI: 10.1029/2018wr023995
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Identification of Snow Melt and Refreeze Events From Passive Microwave Brightness Temperature Using Air Temperature

Abstract: Snow melt and refreeze events are important determinants of spring runoff timing, and snowpack stratigraphy and metamorphism. Previous studies have established the utility of differences between twice‐daily passive microwave brightness temperature (Tb) observations, called the diurnal amplitude variation (DAV), for identifying snow melt and refreeze. Liquid water in snow leads to a large increase in microwave emissivity compared to a completely frozen snowpack, so phase changes from nighttime freezing and dayt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 53 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…This comparison demonstrates the feasibility of using this definition of an observed melt event. Furthermore, other studies have used air temperature as a proxy for melt detection or shown that melt events correspond with air temperature above 0°C (Sturdivant et al, 2019;Tuttle & Jacobs, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This comparison demonstrates the feasibility of using this definition of an observed melt event. Furthermore, other studies have used air temperature as a proxy for melt detection or shown that melt events correspond with air temperature above 0°C (Sturdivant et al, 2019;Tuttle & Jacobs, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Changes in climate, land cover, and population growth in the western United States create a need for more information related to mountain hydrology (Bales et al, 2006). In addition to the main melt onset timing crucial for spring runoff determination, it is also important to have an understanding of winter melting events (Semmens et al, 2013), especially in mid-latitude environments prone to snowpack variations that influence the snow stratigraphy and underlying soil layers (Tuttle & Jacobs, 2019). Satellite-based snowmelt products may decrease the reliance on ground measurements, which cannot capture the spatial and temporal variability of snowpack properties in high-relief and heterogeneous terrain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations